Allele‐aware chromosome‐scale assembly of the allopolyploid genome of hexaploid Ma bamboo (Dendrocalamus latiflorus Munro). Issue 3 (28th February 2022) - Zheng, Yushan; Yang, Deming; Rong, Jundong; Chen, Liguang; Zhu, Qiang; He, Tianyou; Chen, Lingyan; Ye, Jing; Fan, Lili; Gao, Yubang; Zhang, Hangxiao; Gu, Lianfeng
Abstract: Dendrocalamus latiflorus Munro is a woody clumping bamboo with rapid shoot growth. Both genetic transformation and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) gene editing techniques are available for D. latiflorus, enabling reverse genetic approaches. Thus, D. latiflorus has the potential to be a model bamboo species. However, the genome sequence of D. latiflorus has remained unreported due to its polyploidy and large genome size. Here, we sequenced the D. latiflorus genome and assembled it into three allele‐aware subgenomes (AABBCC), representing the largest genome of a major bamboo species. We assembled 70 allelic chromosomes (2, 737 Mb) for hexaploid D. latiflorus using both single‐molecule sequencing from the Pacific Biosciences (PacBio) Sequel platform and chromosome conformation capture sequencing (Hi‐C). Repetitive sequences comprised 52.65% of the D. latiflorus genome. We annotated 135 231 protein‐coding genes in the genome based on transcriptomes from eight different tissues. Transcriptome sequencing using RNA‐Seq and PacBio single‐molecule real‐time long‐read isoform sequencing revealed highly differential alternative splicing (AS) between non‐abortive and abortive shoots, suggesting that AS regulates the abortion rate of bamboo shoots. This high‐quality hexaploid genome and comprehensive strand‐specific transcriptome datasets for this Poaceae family member will pave the way for bamboo research using D. latiflorus as a model species. Abstract : The allele‐aware chromosome‐scale assembly of the genome of the hexaploid Ma bamboo Dendrocalamus latiflorus by Pacific Biosciences Sequel sequencing and chromosome conformation capture sequencing will facilitate overexpression and CRISPRCas9 gene editing studies.